2017
DOI: 10.1016/j.neuroimage.2017.06.078
|View full text |Cite
|
Sign up to set email alerts
|

Inferring synaptic excitation/inhibition balance from field potentials

Abstract: Neural circuits sit in a dynamic balance between excitation (E) and inhibition (I). Fluctuations in E:I balance have been shown to influence neural computation, working memory, and information flow, while more drastic shifts and aberrant E:I patterns are implicated in numerous neurological and psychiatric disorders. Current methods for measuring E:I dynamics require invasive procedures that are difficult to perform in behaving animals, and nearly impossible in humans. This has limited the ability to examine th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

82
1,040
11

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 713 publications
(1,133 citation statements)
references
References 58 publications
82
1,040
11
Order By: Relevance
“…These findings emphasize its physiological origins, and are in line with previous works: arecent study demonstrated that ECoG and EEG electrophysiological neural noise correlates with age and cognitive impairments [21], and it has been associated with an increase in baseline neural spiking activity [28]. It has been hypothesized that increases in the neural noise are a consequence of pathological decoupling between population spiking activity and low-frequency oscillatory neural field [18], and is associated with an imbalance between synaptic excitation and inhibition [29]. Further research is needed to define how background neural activity and oscillatory components interact in PD and how it can affect neural communication in the basal-ganglia-thalamocortical network.…”
Section: Discussionsupporting
confidence: 90%
“…These findings emphasize its physiological origins, and are in line with previous works: arecent study demonstrated that ECoG and EEG electrophysiological neural noise correlates with age and cognitive impairments [21], and it has been associated with an increase in baseline neural spiking activity [28]. It has been hypothesized that increases in the neural noise are a consequence of pathological decoupling between population spiking activity and low-frequency oscillatory neural field [18], and is associated with an imbalance between synaptic excitation and inhibition [29]. Further research is needed to define how background neural activity and oscillatory components interact in PD and how it can affect neural communication in the basal-ganglia-thalamocortical network.…”
Section: Discussionsupporting
confidence: 90%
“…A computational model that incorporated the differential time constants of glutamatergic (AMPA) and GABAergic synaptic currents found that a reduction in the E:I ratio led to more negatively sloped PSDs, while an increased ratio was associated with slope flattening (Gao et al, 2017; but see Lombardi et al, 2017). Corroborating evidence comes from the observation that the PSD becomes more negatively sloped in electrocorticographic (ECoG) recordings of rhesus monkeys undergoing propofol-induced sedation (Gao et al, 2017).…”
Section: Changes In Eeg Multiscale Entropy and Power-law Frequency mentioning
confidence: 99%
“…If a considerable proportion of the variance of band ratios measures is due to aperiodic 661 properties, and not well described or interpreted as band specific changes, then it becomes an 662 open question to ask what the physiological interpretation should be, and therefore how these 663 findings should be interpreted. One hypothesis is that the aperiodic properties of neural time series 664 may relate the relative balance of excitatory and inhibitory activity(Gao et al, 2017). Though further 665 work is required to explore this hypothesis and how it relates to measurements done with band 666 ratios, this does suggest a potential link between what has been measured in band ratios, as a 667 correlate of various cognitive markers and disease states, and potential interpretations related to 668 excitation and inhibition.…”
mentioning
confidence: 99%